Discourse Markers in Hausa Proverbs: Exploring Intellectual Wise Saying from African Wisdom and Culture - Kiyawa, Haruna Alkasim (REiLA : Journal of Research and Innovation in Language, 2021)
This paper aims to explore some intellectual wise saying from African wisdom and culture from one of the three major languages in the northern part of Nigeria. The use of discourse markers is one of the linguistics devices embedded in Hausa proverbs. However, Africa as the continent was occupied by different languages and dialectics. Proverbs is an expression of a saying which combines various wisdom and culture of every human beings living on the earth. This paper utilises written document as a method and selected (36) different proverbs and analyses the discourse markers. Moreover, the paper reviewed various studies that looked at proverbs' role as one of a figurative speech and the definitions of discourse markers defined by literary scholars and cultural critics who studied proverbs from different perspectives. The finding of this paper identified (19) out of (36) proverbs also indicated DMs served as interpersonal functions and the relationship between the speakers’ actions and thoughts, while the remaining (17) functions as textual features for making meaning. Finally, the study found that discourse markers enhance some lexical expressions under different levels, including sentence connectivity, language use, and the appearance of discourse markers in the proverbs. The study's significance shows that cultural scholars and English language educators can incorporate/integrate proverbs and highlighted the role of discourse markers to the student, enhancing their linguistics knowledge, communication skills and learning activities.